Pengaruh Naungan Terhadap Aktivitas Fotosintesis Dan Hasil Produksi Tanaman Cabai Merah (Capsicum Annuum L.) - Helmin Parida Zebua; Herni Jelita Halawa; Stefani Angel Kristin Hulu; Siska Natalia Zebua; Putra Zato Mendrofa (CV. SINAR HOWUHOWU, 2026)
This study aimed to analyze the effect of shading on the growth and photosynthetic rate of red chili pepper (Capsicum annuum L.). The results showed that shading treatment had a significant effect on morphological parameters, namely plant height and total dry weight, but did not significantly affect leaf width, leaf number, and leaf length compared to plants grown without shading. Physiologically, shading influenced quantum yield, photochemical quenching, and non-photochemical quenching, whereas the maximum photosynthetic rate (Pmax) did not show a significant difference. From an ecophysiological perspective, shading treatment significantly increased proline and ascorbic acid contents. These findings indicate that red chili pepper exhibits a high adaptive capacity to low light intensity conditions. This study is expected to contribute as a reference material and learning resource in the fields of plant physiology and plant biology.